2020
DOI: 10.1111/all.14206
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of nasal reactivity to allergens with and without IgE sensitization in patients with allergic rhinitis

Abstract: Ibon Eguiluz-Gracia, Ruben Fernandez-Santamaria and Almudena Testera-Montes contributed equally to this work. Clinical Implications: Nasal reactivity to aeroallergens with and without systemic IgE sensitization can coexist in the same rhinitis patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 44 publications
(129 reference statements)
1
59
0
9
Order By: Relevance
“…For these patients, BAT displays 100% positivity with seasonal allergens and 60% positivity with perennial allergens. 101 Overall, NAC can act as a gold standard in distinguishing the AR phenotype. And BAT could also be useful as an in vitro tool for LAR/ DAR diagnosis in the daily practice.…”
Section: Clinical Biomarkers Of Allergic Rhinitismentioning
confidence: 99%
“…For these patients, BAT displays 100% positivity with seasonal allergens and 60% positivity with perennial allergens. 101 Overall, NAC can act as a gold standard in distinguishing the AR phenotype. And BAT could also be useful as an in vitro tool for LAR/ DAR diagnosis in the daily practice.…”
Section: Clinical Biomarkers Of Allergic Rhinitismentioning
confidence: 99%
“…In this regard, outdoor allergens, such as grass and tree pollens, are normally the main sensitizing allergens for SAR, whereas indoor allergens, such as dust mite allergens are the sensitizing allergens for PAR. 1,2 Recent studies have found different allergens to be prevalent in different regions. For example, birch and grass pollen are the two most common allergens in Denmark, 3 Japanese cedar pollen (JC) is most common in Japan, 4,5 and artemisia pollen is the main allergen in northern China.…”
Section: Environmental Fac Tor Smentioning
confidence: 99%
“…14 Sometimes, environmental factors may not only induce AR, but may also aggravate AR. 2 In particular, an increase in air pollutants in the environment has been found to be associated with increased incidence of allergic respiratory diseases 15 ; with one study in children demonstrating that exposure to oxidizing pollutants in the air leads to a higher risk of developing AR in these children. 16 There is evidence that exposure to the particulate matter (PM2.5) in the environment may increase the degree of DNA methylation in the body.…”
Section: Environmental Fac Tor Smentioning
confidence: 99%
“…It is noteworthy that a proportion of patients displaying nasal reactivity do not exhibit systemic sensitization evidenced by negative skin prick tests (SPT) and undetectable serum-specific IgE (sIgE), an endotype consequently defined as local AR (LAR) [14,15]. Recent evidence shows that both sensitization patterns in response to different allergens can coexist within the same individual, the proposed term for which is dual AR (DAR) [16].…”
Section: Introductionmentioning
confidence: 99%